Transactions Using E-Wallets: How Is the Perspective of Islamic Economics? - Tira Nur Fitria; Yuwita Ariessa Paravasanti; Iin Emy Prastiwi (ITB AAS INDONESIA Surakarta, 2022)
The development of the digital economy presents a variety of transactions and new financial service products that are increasingly diverse. Doing any transactions by using an E-wallet seems to need to be responded to by an Islamic/Sharia economics view. By looking at the perspective of Islamic economics, we as a society will be able to assess how it plays a role in the development of the digital economy. The purpose of this research is to describe the use of E-wallet in doing transactions based on the perspective of Economics in doing transactions. This research is library research. The result analysis shows that digital wallets are something new in the payment system. The digital wallet in Islamic economics is permissible because it makes it easier for people to transact in daily life when they do not carry cash. In the view of Islam, especially the field of muamalat, it holds the principle of